Analisis Kandungan Logam Berat Pb, Cu Dan Zn Pada Daging Dan Cangkang Kerang Kepah (Meretrix Meretrix) Di Perairan Bagan Asahan Kecamatan Tanjung Balai Asahan - Silalahi, Herrys V; Amin, Bintal; ', Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in January 2014 in the waters of Tanjung Balai Asahan Subdistrict Bagan Asahan. The purpose of this study was to determine the content of heavy metals Pb, Cu and Zn that are present in flesh and shells by size, to determine the relationship of heavy metal content in the meat and shells of different sizes and to determine the feasibility of shellfish (M. meretrix)consumption. Content of heavy metals Pb, Cu dan Zn in shellfish (M. meretrix) was analyzed by the dry method used by et all. (2003) The results showed that Pb content in the shell was higher than in the flesh(sig.<0.05), while Cu and Zn higher in the flesh than in the shell(sig.<0.05). Based on body size, Pb in flesh washigher in medium size (1.16 mg/g) and for the other metals were higher in largersize, namely Cu (24.57 mg/g) and Zn (1619.17 mg/g). In the shell, for Pb and Cu were higher in largersize, namely Pb (5.50 mg/g) and Cu (12.33 mg/g), while Zn was higher in small size (434.58 mg/g).Keywords: Pb, CuandZn; M.meretrix; Bagan Asahan